Diffuse Muscular Pain, Skin Tightening, and Nodular Regenerative Hyperplasia Revealing Paraneoplastic Amyopathic Dermatomyositis due to Testicular Cancer. (17th December 2012) - Norrenberg, Sarah; Gangji, Valérie; Del Marmol, Véronique; Soyfoo, Muhammad S.
Abstract : Paraneoplastic dermatomyositis (DM) associated with testicular cancer is extremely rare. We report the case of a patient with skin tightening, polymyalgia, hypereosinophilia, and nodular regenerative hyperplasia revealing seminoma and associated paraneoplastic DM.